Kajian Team Performance Melalui Creative Thinking Sebagai Moderating Variable - Muzalfitri, Eka (Jurnal Keuangan dan Bisnis, 2023)
This study aims to analyze the effect of work climate and leadership on team performance through creative thinking as a moderating variable. It used quantitative research analysis by taking a total sample of 408 respondents using probability sampling in terms of a simple random sampling technique with a population of 1,000 respondents as permanent foundation lecturers at private colleges in the Province of Daerah Istimewa Yogyakarta. The analysis technique used is inferential and descriptive statistics using the concept of Structural Equation Modeling (SEM) assisted by software such as the WarpPLS and SmartPLS programs. The results of this study show that work climate has a negative influence on team performance, while leadership has a positive effect on team performance. The role of the moderating variable in the form of creative thinking indirectly strengthens the influence of climate and leadership on team performance. The results of the analysis infer that the work climate and leadership carried out in the private college have positive or negative effects on the team performance of the lecturers. However, it will be stronger if it is accompanied by adaptive and sustainable creative thinking so that the team performance of the lecturers is more highly improved.